Learning barriers in adopting ICT among selected working women in Malaysia - Hashim, Junaidah (Emerald Group Publishing Limited, 2008)
Purpose – The purpose of this study is to identify learning barriers in information communication technology (ICT) adoption among working women in Malaysia. Regardless of gender, it would be advantageous for all individuals in today’s society to acquire basic ICT skills. Despite significant growth in ICT professionals during the last two decades, there remains a gender imbalance, particularly in developing countries such as Malaysia. Design/methodology/approach – The study uses a self-developed questionnaire to measure the learning barriers and ICT adoption. The survey instrument was developed from the constructs used in the individual innovativeness theory and theory of perceived attributes. The questionnaires were administered face-to-face to a total of 315working women, who participated as respondents in this study. Findings – The findings revealed that the working women in Malaysia possess only average level of ICT skills. They seldom use the internet and e-mail at their workplace or at home, they do not face serious learning barrierswith respect to ICT, and they have complexity as their innovation characteristics. However, they are innovators in the adopters’ categories. The combined variance in the characteristics of learning barriers, ICT skills, and ICT usage amounted to 70 per cent in innovation characteristics. Practical implications – This study reduces the knowledge gap regarding the identification of learning barriers, ICT skills, and ICT usage as predictors of ICT adoption among working women in Malaysia. These factors have been overlooked by some previous researchers. This study also calls attention to the fact that employers and training agencies that are responsible to provide ICT training to women employees must understand and employ the proper learning approaches and methods that ought to be used in adult training and education. Malaysian women are able to adopt an innovation with a high degree of uncertainty at the time of adoption, and it is believed that with correct and suitable training schemes Malaysian working women can acquire appropriate ICT skills and become competent in using ICT at the workplace. With managerial skills and ICT-based competencies, the working women would have a lot more knowledge seeking skills, increased access to up-to-date information, be effective in decision making, and establish networking and linkages. With this they will stand a better chance for promotion and advancement. Originality/value – The sample of this study is unique. This study was conducted in a multi-ethnic, multi-cultural and multi-lingual society. Malaysia presents an interesting case study on working women because it is a society undergoing rapid changes from its strong traditional religious and cultural norms to modern values about women. Keywords Communication technologies, Gender, Learning, Information literacy, Women, Malaysia